Evaluation of hospitalization costs for diabetic pregnant women in a University Hospital in the interior of São Paulo State = Avaliação de custos das internações de gestantes diabéticas de um Hospital Universitário do interior de São Paulo - Silvana Andréa Molina Lima; Ana Cláudia Molina Cavassini; Ligia Nogueira Manso; Marilza Vieira Cunha Rudge (Universidade Estadual de Maringá, 2012)
This study aimed at identifying the hospitalization costs of pregnant women with Diabetes Mellitus (DM) at a University Hospital. It is an observational, quantitative study with descriptive data analysis. The direct and indirect costs available in the institution were identified in order to determine the hospitalization costs for patients diagnosed with DM during pregnancy and childbirth. By means of descriptive statistics, it was observed that 63.46% of the patients had caesarean delivery; the mean total cost was R$ 362.93 (U$ 218.10)/hospitalization during pregnancy, R$ 2,642.65 (U$ 1,588.13)/hospitalization for caesarean delivery, and R$ 2.319.77 (U$ 1,394.09)/hospitalization for vaginal delivery. It was concluded that the analysis of hospitalization costs for patients with DM is of utmost importance, since they are high-complexity hospitalizations that require a large number of interventions, increasing thus the service costs. O trabalho teve como objetivo identificar os custos das internações de gestantes portadoras de Diabetes Mellitus (DM) de um Hospital Universitário. Trata-se de um estudo observacional, quantitativo com análise descritiva dos dados. Foram identificados os custos diretos e indiretos disponíveis na instituição para a determinação dos custos das internações de pacientes com diagnóstico de DM durante a gestação e no parto. Por meio de análise estatística descritiva, verificou-se que 63,46% das pacientes realizaram parto cesárea; o custo médio total foi de R$ 362,93/internação durante a gestação, R$2642,65/internação para o parto cesárea e R$2319,77/internação para o parto vaginal. Conclui-se que é extremamente importante a realização da análise dos custos das internações de pacientes com DM, pois são internações de alto risco, que requerem grande número de intervenções, aumentando os custos do serviço.